Reconciling the divide: A chat with Bill Drayton on social inclusion - Prabhakar, Tamara (Institutional Knowledge at Singapore Management University, 2018)
Within the confi nes of day-to-day routines, it is often diffi cult to cognitively grasp the exponential rate at which the social and industrial sectors are changing. In recent years, the rising prominence of social entrepreneurship is trending as an evolved, levelling collaborative model for solving social problems more effectively than traditionally rigid hierarchical structures of management. Social entrepreneurs hold the distinct ability to innovate and form novel solutions based on their fi rst-hand cultural knowledge and experiences rather than from popular generalised perceptions or indirect comprehension of situations from diffused information.